2013
DOI: 10.1163/22941932-00000005
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Fibre Length and Ray Dimensions to Sound Propagation velocity in wood of selected Tropical Hardwoods

Abstract: this study investigates the relation of fibre length and ray dimensions to the sound propagation velocity in four commercial tropical hardwoods. The species used in the study were Doussié (Afzelia bipindensis Harms), Merbau (Intsia bijuga (Colebr.) Kuntze), Muiracatiara (Astronium graveolens Jacq.) and Wengé (Millettia laurentii De Wild.). The sound propagation velocity was established by the frequency-resonance method. A positive correlation was obtained between fibre length and sound velocity within species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…There are different reports about the relationship between FL and acoustic velocity in hardwood species. Similar to the results presented in this study, Baar et al (2013) reported a low correlation (r = 0,45) between FL of wenge (Millettia laurentii) De Wild and ultrasound velocity. In contrast, Van Duong et al (2019) obtained a moderate relationship (r = 0,69) for chinaberry tree (Melia azedarach L.) wood, while Polge (1984) reported a higher relationship (r = 0,90) for cherry wood.…”
Section: Sd Is Standard Deviation; CV Is the Coefficient Of Variationsupporting
confidence: 90%
“…There are different reports about the relationship between FL and acoustic velocity in hardwood species. Similar to the results presented in this study, Baar et al (2013) reported a low correlation (r = 0,45) between FL of wenge (Millettia laurentii) De Wild and ultrasound velocity. In contrast, Van Duong et al (2019) obtained a moderate relationship (r = 0,69) for chinaberry tree (Melia azedarach L.) wood, while Polge (1984) reported a higher relationship (r = 0,90) for cherry wood.…”
Section: Sd Is Standard Deviation; CV Is the Coefficient Of Variationsupporting
confidence: 90%
“…It can be explained by several reasons. The acoustic wave velocity can be affected by the moisture content, temperature, grain orientation, density, decay, and also geometry (Beall 2002) and by the length of fibers and ray dimensions (Baar et al 2013). The difference in velocity can be caused by a different anatomical structure of spruce and oak (Saadat-Nia et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In hard woods, the longitudinal elements oriented parallel to the axial direction provide strength for the tree as well as a continuous path for wave propagation. The indispensable role of fibre length in acoustic behaviour of wood has been reported by various researchers (Feeney 1987;Hasegawa et al 2011;Baar et al 2013). However, in radial and tangential directions, the lack of continuous path was observed similarly in longitudinal directions, making a kind of stop banding for wave movement.…”
Section: Discussionmentioning
confidence: 77%